Hedging, Hedge Accounting, and Audit Fees - Hsu, Pei-Hui; Jan, Ching-Lih; Tan, John (Journal of Accounting and Finance, 2020)
Derivative financial instruments have been used as a tool to hedge risk. Due to the complex accounting rules for derivative contracts, more audit work is required. This study examines audit fees for firms that have derivative-related data from 2013 to 2017. We find that when firms with foreign operations, a high amount of debt, and a poor credit rating face higher market risks; audit fees are actually negatively related to the amount of derivatives used. We do not find positive correlation between audit fees and the additional audit work required for the cash flow hedge designation to be significant.